Phenology Growth and Yield of Sesamum (Sesamum Indicum L.) in Relation to Rainfall and Temperature - Pandey, Vyas; Jambukia, T K; Patel, A T; Sharma, A N (Annals of Arid Zone, 2016)
Study on phenology, growth and yield of sesamum (Sesamum indicum L.) revealed that the correlation coefficient between growing degree days (GDD) and plant hight, leaf area and total drymatter production were 0.91,0.93 and 0.82, respectively. About 281 GDD were needed for emergence of sesamum seed and about 31 GDD were required to produce I g drymatter. The rainfall growing degree days (RGDD) was better than GDD in explaining the phenological stages i.e. 50% flowering and maturity of sesamum crop.